Early College High Schools at Scale: Using Administrative Data to Assess the Impacts of an Educational Intervention on Voting and Crime - Lauen, Douglas; Fuller, Sarah; Swiderski, Tom; Unlu, Fatih (International Journal of Population Data Science, 2018)
Early college high schools (ECHS) are small schools of choice which provide students with the opportunity to earn, at no financial cost to them, two years of transferable college credit or an associate's degree while simultaneously satisfying high school graduation requirements. This promising intervention is aimed at smoothing the transition from high school to college for under-represented minorities and students from economically disadvantaged backgrounds. There are about 80 ECHS in North Carolina, although the model is implemented in many other states as well. While much is known from prior research about the impacts of the intervention on educational attainment, nothing is known about longer term outcomes such as employment, wages, criminal involvement, and voting behavior. The present study will briefly describe the data collection process, research methods, and preliminary findings on the effects of the intervention on voting and criminal conviction in North Carolina. We will also present results on whether impacts on long term civic outcomes are mediated by educational attainment. Quasi-experimental impacts have been validated against impacts generated from a randomized controlled trial of the same intervention in a subset of the sites during the same time period. The team assembled personally-identified population level statewide administrative data on all NC high school students (including ECHS) and linked it to records housed at community colleges, universities, the Department of Public Safety (incarceration), and Board of Elections (voting). Together this effort comprises one of the more comprehensive administrative data collection efforts linking student level K-12, postsecondary, and longer-term outcomes.